2014
DOI: 10.1177/1049909114523826
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Canadian Hospice Palliative Care Volunteers’ Attitudes Toward Physician-Assisted Suicide

Abstract: The purpose of this study was to examine the attitudes of hospice palliative care (HPC) volunteers who provide in-home support (n = 47) and members of the community (n = 58) toward the issue of physician-assisted suicide (PAS). On the first part of the survey, participants responded to 15 items designed to assess their attitudes toward PAS. An examination of individual items revealed differences in opinions among members of both the groups. Responses to additional questions revealed that the majority of volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Conversations and requests for assistance in death are commonly experienced by healthcare providers, including nurses, and are well documented across a diverse range of clinical settings [ 17 , 22 , 35 ]. For example, approximately 1 in 5 hospice volunteers reported that a patient had initiated discussions about assisted death [ 14 ], while studies of nurses demonstrate the frequent and often morally challenging interactions that exist with patients requesting assistance to end their life [ 26 ]. When reflecting upon the evolving separation that occurs upon a request for MAiD within non-providing hospice contexts, some participants perceived this as a failure or rejection of hospice care provision due to their inability to fully support the patients’ needs.…”
Section: Discussionmentioning
confidence: 99%
“…Conversations and requests for assistance in death are commonly experienced by healthcare providers, including nurses, and are well documented across a diverse range of clinical settings [ 17 , 22 , 35 ]. For example, approximately 1 in 5 hospice volunteers reported that a patient had initiated discussions about assisted death [ 14 ], while studies of nurses demonstrate the frequent and often morally challenging interactions that exist with patients requesting assistance to end their life [ 26 ]. When reflecting upon the evolving separation that occurs upon a request for MAiD within non-providing hospice contexts, some participants perceived this as a failure or rejection of hospice care provision due to their inability to fully support the patients’ needs.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care volunteers in home care, community and stand-alone hospice settings have been the focus of some research interest over the years, focusing on the nature of the volunteer role, 15 the experiences and motivations of volunteers, 16 the impact of volunteering on the volunteer, 17 ethical challenges associated with volunteering 18,19 and volunteers' interactions/relationships with professional staff. 20 A recent systematic review confirmed that the volunteer role was distinctly different from that of paid staff, such as health professionals, characterised by the social nature of the role and volunteer-patient relationships, across home care, hospice and palliative care unit settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although many hospice palliative care volunteers also volunteer for other organizations, 28 they appear to be less prone to burnout compared to paid hospice palliative care staff members. 29 For the most part, volunteers do not generally perceive their hospice palliative care work as stressful and any stressors/ challenges they do encounter tend to be temporary or not long lasting 1,2 and are more likely to affect new or inexperienced volunteers who are still ''learning the ropes.''…”
Section: Resultsmentioning
confidence: 99%